STAGES OF GRIEF IN KATHLEEN GLASGOW “HOW TO MAKE FRIENDS WITH THE DARK” - Winardi, Yohanes Kurniawan; Subianto, Audrey Eveline (Universitas Putera Batam, 2023)
The grieving process, as described in the book